2018
DOI: 10.4172/2472-1115.1000128
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Adults with Down syndrome in Virginia

Abstract: Background: Quality of Life (QOL) has been developing in the field of intellectual development disability since the early 1980s, and ever since there have been research, models, and theoretical constructs along with many recommendations. Ignored in its early development, QOL is now seen as important for support and intervention. Down syndrome is the most common occurring chromosomal condition-one in 700 babies in the USA is born with it. Limited research has been conducted to study quality of life of adults wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Four studies obtained self-reports with minimal support from the proxies [ 70 73 ]. Eleven studies collected proxy reported QoL from caregivers [ 74 84 ] and 16 from a combination of self and proxy reports [ 85 100 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies obtained self-reports with minimal support from the proxies [ 70 73 ]. Eleven studies collected proxy reported QoL from caregivers [ 74 84 ] and 16 from a combination of self and proxy reports [ 85 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 24 studies focused on the personal development of adults with DS. Four self-reported [ 62 , 64 , 65 , 68 ], two parent-proxy reports [ 74 , 76 ] and four studies using both self-and proxy-reported [ 90 , 93 , 95 , 100 ] examined the educational status of adults with DS who had attended mainstream schools and further education colleges. Two studies [ 76 , 90 ] reported that adults with DS were in their late 30s at the time of the study and in school, with 79% reading and/or look through books at least once a week [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DS occurs approximately in 1 out of 700 live births and predominantly in 15% of children aged 3-17 (American Psychiatric Association, 2013). Children with this characteristic condition experience deficiency in intellectual capacity (Allahyari & Wolf-Branigin, 2018), limitations in intellectual and adaptive behaviors (Fidler et al, 2009;Schalock et al, 2007), difficulty in problemsolving (Fidler et al, 2011), shortened life spans (Allahyari & Wolf-Branigin, 2018), language expression and motor development impairment (Daunhauer & Fidler, 2011;Mbugua et al, 2011).…”
Section: Introductionmentioning
confidence: 99%